Interaction of proteins involved in ecdysone and juvenile hormone signal transduction. - Bitra, K.; Palli, S.R. (Archives of Insect Biochemistry and Physiology, 2009)
Ecdysteroids and juvenile hormones (JH) regulate a variety of developmental, physiological, behavioral, and metabolic processes. Ecdysteroids function through a heterodimeric complex of two nuclear receptors, ecdysone receptor (EcR) and ultraspiracle (USP). An 85 kDa protein identified in Drosophila melanogaster methoprene-tolerant (Met) mutant binds to JH III with high affinity, and the mutant flies are resistant to juvenile hormone analog (JHA), methoprene. Reporter assays using the yeast two-hybrid system were performed in order to study the molecular interactions between EcR, USP and Met. As expected, EcR fused to the B42 activation domain and USP fused to the LexA DNA binding domain interacted with each other and supported induction of the reporter gene in the presence of stable ecdysteroid analog, RG-102240 or steroids, muristerone A and ponasterone A. The USP:USP homodimers supported expression of the reporter gene in the absence of ligand, and there was no significant increase in the reporter activity after addition of a JHA, methoprene. Similarly, Met:Met homodimers as well as Met:EcR and Met:USP heterodimers induced reporter activity in the absence of ligand and addition of ecdysteroid or JH analogs did not increase the reporter activity regulated by either homodimers or heterodimers of Met protein. Two-hybrid assays in insect cells and in vitro pull-down assays confirmed the interaction of Met with EcR and USP. These data suggest that the proteins that are involved in signal transduction of ecdysteroids (EcR and USP) and juvenile hormones (Met) interact to mediate cross-talk between these two important hormones. Arch. Insect Biochem. Physiol. 2008. (c) 2008 Wiley-Liss, Inc.